Model Optimalisasi Daya Saing UMKM Di Kota Tasikmalaya Melalui Pendekatan Analytical Hierarchy Process - Barlian, Barin (Journal of Business Management Education (JBME), 2023)
The objectives of this research are 1) to conduct an analysis of the competitiveness of MSMEs in Tasikmalaya City, 2) to formulate a strategy to increase the competitiveness of MSMEs in Tasikmalaya City 3) Develop a strategy model for MSME competitiveness in Tasikmalaya City. The target of the findings in this study is to develop a competitive strategy model adopted from Porter's strategy model. This research was carried out through a strategy formulation approach using the Analytical Hierarchy Process (AHP) method. The respondents in this research were MSME actors spread across 10 (ten) sub-districts in Tasikmalaya City using purposive sampling technique. Based on the AHP analysis, it was found that the priority strategy that must be carried out by MSMEs in Tasikmalaya City is to use modern equipment, wider business coverage (domestic and foreign), establishing collaboration with government and private parties. The suggestion in this study is to carry out good cooperation between MSMEs and the government (triple helix) so that MSMEs can carry out their roles well and create good MSME competitiveness as well.